Translation, Gender, and Legitimacy – A Study of Review Excerpts - Axelsson, Marcus (Tidskrift för litteraturvetenskap, 2023)
This article focuses on translation, gender, and cultural legitimacy. Some studies touching on these topics have been carried out previously, but few have analyzed how translated novels are paratextually designed for marketing purposes. I aim to bridge this research gap by focusing on review excerpts presented on the covers of novels translated into Swedish. More specifically, I investigate how different aspects of gender affect review excerpts. I draw upon Gino Cattani and colleagues’ (2014) three kinds of legitimacy that a cultural agent may grant to a cultural product. These are bourgeoislegitimacy (recognition from critics), popular legitimacy (recognition from the public), and specific legitimacy (recognition from peers). Methodologically, I use descriptive statistics to describe and analyze a corpus of 333 book covers of translated novels collected in a bookstore in Sweden. I categorize and quantify the review excerpts on the covers according to the three kinds of legitimacy and then discuss a few cases. The results show that review excerpts categorized as bourgeois legitimacy originating from the target culture dominate for both female and male authors. Review excerpts categorized as popular legitimacy are rare in the corpus, but a large majority of occurrences are used on the cover of books written by women. Specific legitimacy, on the other hand, is more widespread among the male authors.